2016
DOI: 10.1186/s12872-016-0320-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipo/cytokines in atherosclerotic secretomes: increased visfatin levels in unstable carotid plaque

Abstract: BackgroundNovel pro-inflammatory and anti-inflammatory derivatives from adipose tissue, known as adipokines, act as metabolic factors. The aim of this study was to analyse the secreted expression of different adipo/cytokines in secretomes of unstable carotid atherosclerotic plaque versus non-atherosclerotic mammary artery.MethodsWe evaluated the secretion levels of adiponectin, visfatin, lipocalin-2, resistin, IL-6 and TNFR2 by ELISA in human secretomes from cultured unstable carotid atherosclerotic plaque (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
1
19
0
3
Order By: Relevance
“…Unstable plaques share some distinctive features such as a thinner fibrous cap overlying a large necrotic core or a strong intraplaque inflammatory reaction 21 , 22 ) . Novel pro-inflammatory and anti-inflammatory derivatives from adipose tissue, known as adipokines, were found to be associated with carotid plaque instability 23 ) . For example, Auguet et al 23 ) reported that visfatin levels were significantly increased in unstable carotid atherosclerotic plaque secretome than in non-atherosclerotic mammary artery secretome.…”
Section: Discussionmentioning
confidence: 99%
“…Unstable plaques share some distinctive features such as a thinner fibrous cap overlying a large necrotic core or a strong intraplaque inflammatory reaction 21 , 22 ) . Novel pro-inflammatory and anti-inflammatory derivatives from adipose tissue, known as adipokines, were found to be associated with carotid plaque instability 23 ) . For example, Auguet et al 23 ) reported that visfatin levels were significantly increased in unstable carotid atherosclerotic plaque secretome than in non-atherosclerotic mammary artery secretome.…”
Section: Discussionmentioning
confidence: 99%
“…48 The use of LITA may alter the magnitude of gene expression differences as it contains adventitia lacking in endarterectomy samples; previously M4 macrophages have been found in the adventitia of atherosclerotic coronary arteries. 47 However, the same setting has been utilised successfully in previous studies, 49,50 and normal histology in LITA, healthy carotid, and abdominal aortic samples was verified. 41 The sample material was skewed towards advanced plaques, which may explain the lack of consistent association with plaque stability markers, that is, stabilisation or thrombosis related genes.…”
Section: Discussionmentioning
confidence: 85%
“…A study by Auguet et al has revealed that the levels of visfatin are substantially higher in the secretome of the unstable atherosclerotic plaque from a carotid artery than in the secretome of a nonatherosclerotic thoracic artery. There were no differences in other analyzed adipo-/cytokines [96]. Of note, in a study by Zheng et al on the level of visfatin in patients with T2DM, the patients were subdivided into two groups by the presence of atherosclerotic plaques.…”
Section: Visfatinmentioning
confidence: 87%